Sri Aurobindo’s Integral Education Philosophy and the National Education Policy 2020: Towards a Holistic and Transformative Education - Sucharita, V. (JOURNAL OF INDIAN EDUCATION, 2026)
The ancient education system of India, was a citadel of knowledge and practices, that not only encouraged humanity but also provided sustainable alternatives for a collective and harmonious life. The very idea of education was rooted in its philosophical aim of enlightenment and raised consciousness. It helped in the holistic development of the physical, intellectual, spiritual, and artistic aspects of life. Several Indian philosophers have illuminated their thoughts on the true essence and meaning of education. One such philosopher is Sri Aurobindo, whose philosophy of integral education is immensely valuable in contemporary times, when an individual’s holistic development is gaining prominence. Education that merely focuses on its instrumental value obscures its fundamental aim, which transcends beyond marks, degrees, and other measurable outcomes. The present paper explicates Sri Aurobindo’s profound thoughts on education and attempts to unfold its overarching significance amidst the backdrop of the changing landscape of education and in the light of the NEP 2020 policy discourse.